Probabilidade de idosos com saúde vascular apresentarem hipertensão arterial sistêmica - Freitas, Ercilhana Gonçalves Batista (2018)
Introduction: Elderly patients with normal systemic arterial blood pressure associated with femoral carotid pulse velocity (cf-PWV) less than 7.6 m/s and without associated comorbidities are considered with good vascular health. Objectives: To verify the probability that elderly patients with good vascular health have at least one blood pressure measurement above the diferente thresholds for systolic blood pressure (120, 130 and 140 mmHg) during two years of follow–up. Methods: We selected 72 normotensive patients (<140/90 mmHg) without comorbidities and divided them into group A, who had cf-PWV < 7.6 m/s (n = 27; 65 ± 4 years), and group B, patients with cf-PWV ≥ 7.6 m/s (n = 45; 66± 8 years). These patients were followed for two years and were observed in 3 outpatient visits (0, 12 and 24 months). At each visit, the brachial pressures were indirectly measured in triplicate, and applanation tonometry was performed. Results: When the group A and group B were compared, the odds ratio (OR) of having a systolic pressure measurement ≥ 140 mmHg in two years of follow-up was 0.22 (p< 0.0001); ≥ 130 mmHg, the OR was 0.49 (p< 0.0007), and ≥ 120 mmHg, the OR was 0.54 (p< 0.001). Group A persisted with low values of cf-PWV (adjusted by age and mean arterial pressure) during the two years of follow-up. The average brachial systolic pressure remained constant during the two years in group A.Conclusions: Vascular health in elderly individuals seems to protect against occasional elevations of systemic arterial pressure.